Review On Design and Development of Phenytoin Rectal Suppository Containing Natural Polymers - Vishal Salunke; Abhijeet Surwase (International Journal of Scientific Research in Science and Technology, 2026)
Rectal drug delivery is an important alternative route for administering drugs, especially in conditions where oral administration is not feasible such as vomiting, unconsciousness, and seizures. Phenytoin is a widely used antiepileptic drug, but its oral and parenteral administration presents several limitations including poor patient compliance and variable bioavailability. The present review focuses on the design and development of phenytoin rectal suppositories using natural polymers. Natural polymers such as alginate, pectin, and xanthan gum are gaining attention due to their biocompatibility, biodegradability, and ability to provide controlled drug release. These polymers play a significant role in enhancing drug stability, improving release characteristics, and increasing patient acceptability. The formulation of suppositories involves careful selection of base, polymer, and preparation method to achieve desired therapeutic outcomes. This review highlights the principles of rectal drug delivery, types of suppository bases, role of natural polymers, formulation techniques, and evaluation parameters such as drug content, melting point, and in vitro drug release. Additionally, recent advances and challenges associated with rectal suppository formulations are discussed. Overall, phenytoin rectal suppositories containing natural polymers represent a promising approach for effective and controlled management of epilepsy, particularly in emergency and pediatric conditions, offering improved bioavailability and better patient compliance.
Keywords: Rectal Drug Delivery; Phenytoin Suppositories; Natural Polymers